THE USE OF SAMPLING IN AUDITIG - ضو د. خليفة (Dirasat in Economics and Business, 2022)
Due to the expansion of the accounting data to be audited, accountants have to use sampling procedures to save time and money. Two types of sampling are discussed in the Arabic version of this article: judgement sampling and statistical sampling. Due to the expansion of business firms in both the public and private sectors, accountants in Libya need to use sampling procedures. It is recommended that the Libyan Accounting Institute consider this subject and arrange for a training program in sampling procedures for Libyan accountants.